Phytochemical, antioxidant, and antimicrobial analysis of Trichoderma asperellum isolated from ascidian Eudistoma sp - Deiske Adeliene Sumilat, Rosita Anggreini Junita Lintang, Suzanne Lidya Undap, Ahmad Akroman Adam, Trina Ekawati Tallei (Journal of Applied Pharmaceutical Science, 2022)
Ascidians and their associated fungi are prolific producers of bioactive natural products. This present study was aimed at examining the characteristics of phytochemicals, antioxidants, and antimicrobial activity of the culturable fungi associated with Eudistoma sp. that were collected from the waters of Bunaken Island, North Sulawesi, Indonesia. Endophytic fungi were isolated using the dilution method on sabouraud dextrose agar supplemented with chloramphenicol. The pure fungal isolates were grown in a rice medium for 15 days under static conditions and daylight at room temperatures. The fungus and the rice medium substrate were extracted with EtOAc, evaporated, and freeze-dried, yielding a dry extract. The antioxidant activities were assessed using the 2,2-diphenyl-1-picrylhydrazyl assay. The antibacterial activity of the ethyl acetate fungal symbiont extract was determined using the Kirby–Bauer disk diffusion method, employing Candida albicans, Staphylococcus aureus, Escherichia coli, Aeromonas hydrophila, and Salmonella sp. as indicator pathogenic microbes. The phytochemical screening revealed the presence of secondary metabolites such as alkaloids, triterpenoids, tannins (1.11 mg/ml), flavonoids (3.76 mg/ml), and phenolics (5.98 mg/ ml) in the fungal extract. The EtOAc extract of the fungus had a moderate antimicrobial activity against C. albicans, E. coli, and S. aureus but a strong antibacterial activity against A. hydrophila and Salmonella sp. Molecular identification using the ITS1-4 region of DNA revealed that the fungal strain had 99.37% identity with Trichoderma asperellum. Hence, this fungus can be further investigated as a potential source of antioxidants as well as broad-spectrum antimicrobials.
Keywords: Ascidian-associated fungus, Trichoderma asperellum, Eudistoma sp., Bunaken, antimicrobial